A numerical study on film condensation of steam with non-condensable gas on a vertical plate - Li, Shanwei; Wei, Min; Wang, Xiaojia (Frontiers in Energy Research, 2023)
The film condensation of steam is very common in several industrial areas, such as condensers in power plants, seawater desalination, and air-conditioning systems. In some studies, the non-condensable gas and liquid film are overlooked for the sake of simplicity. To provide an integral computational scheme, in the present study, the film condensation of steam in the presence of non-condensable gas on a vertical plate has been simulated using a two-dimensional CFD model combining a wall condensation model and volume of fluid (VOF) model. After verification, the proposed computational scheme is used to simulate the steam condensation process, with the mass fractions of non-condensable gas varying from 5% to 45%. The results indicate that the concentration of non-condensable gas in the boundary layer decreases gradually with the condensation process, resulting in a decline in the synergy between temperature and velocity field. It can also be found that the fluctuation of the liquid film can influence the concentration distribution of the non-condensable gas layer. For cases with high concentrations of steam, the thermal resistance of liquid film can reach more than 20% of the total thermal resistance, which should not be ignored.